Who Owns the Space? A Near-Accident Perception Of eScooters Riders in Interaction with Pedestrians - Nikolaou, Paraskevas; Kalisperatos, Argyrios; Nikiforiadis, Andreas; Fountas, Grigorios; Campisi, Tiziana; Basbas, Socrates (My University, 2026)
The rapid growth of e-scooter usage in urban environments has introduced new safety challenges, particularly in shared spaces with pedestrians. This study in-vestigates near-collision interactions between e-scooter riders and pedestrians in a pedestrianized area in Thessaloniki, Greece, based only on 100 observed near-miss incidents. A multidimensional approach is adopted to analyze behav-ioral responses and interaction dynamics. Ordinal Logistic Regression is em-ployed to examine the factors influencing changes in e-scooter speed (accelera-tion, no reaction, and varying levels of deceleration) when riders encounter pe-destrians. Subsequently, behavioral personas for both e-scooter riders and pe-destrians are identified, and a Firth Logistic Regression model is applied to as-sess the likelihood of high-risk conflicts arising from different persona combi-nations. The results reveal that while most riders adopt defensive behaviors, a significant proportion of risky responses persists, particularly in the presence of inattentive or unresponsive pedestrians. The findings indicate that near-collision risk is primarily driven by behavioural interactions, while environ-mental conditions such as congestion further amplify these effects. The results are particularly relevant for urban planners, transport engineers, and policy-makers, as they provide evidence to support the design of safer shared spaces and the development of targeted interventions addressing both rider and pedes-trian behaviour.